1979
DOI: 10.1021/bi00577a016
|View full text |Cite
|
Sign up to set email alerts
|

s-Cis and s-trans isomerism of the His-Pro peptide bond in angiotensin and Thyroliberin analogs

Abstract: The dipeptide His-Pro isomerizes from all-s-trans to partly s-cis when titrated in D2O from acidic to neutral pD as observed by 13C and 1H nuclear magnetic resonance of the proline side chain. This isomerization is reported by the His C-2 and C-4 protons and carbons which show distinct, well-resolved resonances for each isomer. The influence of the His-Pro peptide bond rotational state on the histidine protons far removed from the bond has not been previously observed in model compounds or peptides. The peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…For example, the signals downfield from 6 ppm in the spectrum of IIA are due to tyrosine, while the most downfield resonance in the spectrum of All is due to proton H-2 of histidine. As previously noted (12,13) Fig. 1 b-d.…”
Section: Resultssupporting
confidence: 82%
“…For example, the signals downfield from 6 ppm in the spectrum of IIA are due to tyrosine, while the most downfield resonance in the spectrum of All is due to proton H-2 of histidine. As previously noted (12,13) Fig. 1 b-d.…”
Section: Resultssupporting
confidence: 82%
“…It exhibits different conformational states such as α ‐helix, β ‐turn, γ‐turn, and random coil in aqueous solution and is pH dependent. Angiotensin‐I also shows pH‐dependent cis ↔ trans isomerization in His 6 ‐Pro 7 to effect its bioactivity . The interaction of different metal ions with AngI gained significant attention because the metal cations cease such isomerization.…”
Section: [Angiotensin‐i‐(n‐1)h + Ncui] and [Angiotensin‐i‐(2n‐1)h + Nmentioning
confidence: 99%
“…Structure-activity relationships studies from several laboratories have revealed the topological contribution of the individual amino acid residues of the active AII molecule [3][4][5]. These studies have included theoretical [6,7] physicochemical [8,9], and spectroscopic investigation [10][11][12][13][14][15][16] and have led to several models for the AII structure in solution. However, a great variety of structural features such as a helix [8,17,18,] b pleated sheet, b and c turn [15,19], charge relay [20,21] and other structures [6,22] have been proposed.…”
mentioning
confidence: 99%